Effect of a Copaiba Oil-Based Dental Biomodifier on the Inhibition of Metalloproteinase in Adhesive Restoration - Eliane Avany Malveira Araújo; Geisy Rebouças Lima; Luciana Aleixo dos Santos de Melo; Leilane Bentes de Sousa; Marne Carvalho de Vasconcellos; Nikeila Chacon de Oliveira Conde; Carina Toda; Simone Assayag Hanan; Ary de Oliveira Alves Filho; Maria Fulgência Costa Lima Bandeira (Hindawi Limited, 2021)
Aim. This study sets out to evaluate the antiproteolytic activity of copaiba oil-based emulsion at the resin/dentin adhesive interface union formed with conventional and self-etching adhesives systems. Methods. At in situ zymography, 30 teeth were sectioned 2 mm below the enamel-dentin junction; a smear layer was standardized and subdivided into four groups. Gelatin conjugated with fluorescein was used and taken to the fluorescence microscope for evaluation. In cytotoxicity, the Trypan Blue method was used at four different time points. The tested groups were (G1) control with distilled water; (G2) 2% chlorhexidine (CLX); (G3) emulsion based on copaiba oil (EC) 10% + X; (G4) 10% EC + Y; and (G5) EC 10% alkaline. The zymographic assay used the same groups described, but in 30 seconds and 10 and 20 minutes. HT1080 cells were incubated and submitted to electrophoresis. The gel was analyzed using ImageJ software. Mann-Whitney and Kruskal-Wallis tests were used in the statistical analysis (p<0.05). Results. ECs showed higher cell viability in the cytotoxicity test and showed a significant difference in 10 and 20 minutes. In the zymographic assay, alkaline EC reduced 67% of MMP-2 activity and 44% of MMP-9 compared to 2% chlorhexidine. At in situ zymography in qualitative evaluation, all groups tested showed inhibition of activity in metalloproteinases. Conclusion. EC showed activity in the inhibition of metalloproteinases in vitro and in situ, especially the alkaline one. The survey shows the possibility of using ECs, a product from Amazonian biodiversity, as a biomodifier in dentistry.